Differences Between General Internal Medicine and Family Medicine Physicians' Initiation of Pre-Exposure Prophylaxis - Theresa Drallmeier; Joanne Salas; Elizabeth Keegan Garrett; Ashley Meyr; Jane Tucker; Jeffrey F. Scherrer (SAGE Publishing, 2023)
Objective: Preexposure Prophylaxis (PrEP) is under-utilized in primary care. Given differences in treatment approaches for other conditions between family medicine (FM) and general internal medicine (GIM), this study compared PrEP-prescribing between FM and GIM physicians. Methods: De-identified electronic health record data from a multi-state health care system was used in this retrospective observational study. The time period from 1/1/13 to 9/30/21 was used to identify PrEP eligible patients using measures of current sexually transmitted disease and condomless sex at the time of eligibility. Receipt of PrEP was measured in the 12 months after PrEP eligibility. The odds of receiving PrEP in GIM as compared to FM was computed before and after adjusting for demographics and physical and psychiatric comorbidities. Results: The majority of eligible patients were 18 to 39 years of age, 60.9% were female and 71.6% were White race. Among PrEP eligible patients, 1.1% received PrEP in the first year after index date. Receiving PrEP was significantly more likely among patients treated in GIM versus FM (OR = 2.30; 95% CI:1.63-3.25). After adjusting for covariates, this association remained statistically significant (OR = 2.02; 95% CI:1.41-2.89). Conclusions: PrEP is grossly under-utilized in primary care. The majority of Americans enter the health care system through primary care and not through HIV providers or other specialties. Therefore, educational interventions are needed to increase confidence and knowledge and to encourage PrEP prescribing by FM and GIM physicians.